DEVELOPMENT OF A RESIDENT ATTITUDE SCALE TOWARD TOURISM IN LANGKAWI: COMPARING EASTERN AND WESTERN CONTEXTS - MOHD. SHARIFF, NURHAZANI (ASEAN Journal on Hospitality and Tourism, 2005)
The purpose of this paper is to review and compare the development of an attitudinal scale for measuring residents? attitudes toward tourism in the context of the Eastern and Western community.To date, two standardized scales which focused on the Western community were developed by Lankford and Howard (1994) and Ap and Crompton (1998). None, however, has been developed in the context of the Eastern community. Since both the communities have different culture and beliefs toward certain aspects, the development of the scale is important in order to understand resident attitudes. Thus, a study was undertaken in Langkawi Island, Malaysia for the purpose ofdeveloping the scale and the results were compared with the existing scale. Several similarities and differences of items are found in the scale developed for both the Eastern and Western contexts.